Find the possible value of k for which the equation m = 1 ∑ k ( x + m − 1 ) ( x + m ) = 1 0 k has a solution α and α + 1 for some α .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yeah. There are many problems which are similar to each other throughout brilliant
( y − 1 ) y = 3 3 ( y − 1 ) y = 3 y 3 − ( y − 1 ) 3 − 3 1 ∴ 1 0 k = 3 1 [ m = 1 ∑ k { ( x + m ) 3 − ( x + m − 1 ) 3 } − m = 1 ∑ k 1 ] ⇒ 1 0 k = 3 1 [ ( x + k ) 3 − x 3 − k ] = 3 1 [ 3 k x 2 + 3 k 2 x + k 3 − k ] ⇒ 3 x 2 + 3 k x + k 2 − 3 1 = 0 & ( α − β ) 2 = ( α + β ) 2 − 4 α β = k 2 − 4 3 k 2 − 3 1 = 3 − k 2 + 1 2 4 ⇒ 1 = 3 − k 2 + 1 2 4 ⇒ k = 1 1
Correction k = 1 1
Log in to reply
Thanks,edited.
But why -11 is not the answer?Am i missing something?
Log in to reply
k is the upper bound in the summation. Hence it cannot be negative.
Problem Loading...
Note Loading...
Set Loading...
This Problem is same as;
Keep it up ; By....Akshat Sharda,